The Dynamic of Density and Diversity of Cyanophyta in Different Pond Bases in Educational Pond of Faculty of Fisheries and Marine Universitas Airlangga - S Z Cahyani (2019)
This study was conducted in tarpaulin and soil base educational pond in the Faculty of Fisheries and Marine Universitas Airlangga. This study is aimed to know the dynamics of density and variety of Cyanophyta in ponds of different bases at educational ponds of Faculty of Fisheries and Marine Universitas Airlangga. The research employed survey method, which is intended to describe the existing phenomena, regardless the period of occurrence. The results were presented in descriptive form. The result of observed density of Cyanophyta at 14.00 in the tarpaulin pond ranged between 868,000 and 1,569,000 ind / l., while the one in the soil pond ranged from 331,000 to 372,000 ind / l. The result of observed dynamics in the tarpaulin pond included the species of Ghomphosphaeria, Anabaena circularis, Anabaena raciborskii, Anabaena sphaerica, Microcystis sp., and Spirulina sp. On the other hand, in the soil pond were Anabaena circularis, Anabaena raciborskii, Microcystis sp., and Spirulina sp. Spirulina sp was the dominant species in the tarpaulin and soil ponds.